Analisis Kinerja Pembangkit Listrik Tenaga Biomasa Sawit (PLTBS) Pabatu PT Perkebunan Nusantara IV - Saptyaji Harnowo (Jurnal Mekanika dan Sistem Termal, 2016)
Palm Oil Biomass Power Plant (PLTBS) in Pabatu Estate, North Sumaterahas been in operation since 2010. The plant is planned to generate power up to 3.2 Mwatt with waste fuel from empty fruit bunches palm oil. Since this operation, the performance of this biomass power plant ( PLTBS) not reachsits target as designed. Electric power generated is under rated capacity and the fuel can not use empty fruit bunches, and changes by oil palm shell that has a higher economic value. This study aims to analyze and audit the performance of biomass power plant/PLTBS Pabatu. Analysis was conducted on the performance of each equipment operational parameter that was collected during this study. These equipment are: boiler, turbine, generator, condenser and pump in accordance with the Rankine cycle. Data operational calculated based on Thermodynamic analysis with the results show the performance of PLTBS Pabatu still not optimal. Thermal efficiency is still low about 22%, boiler efficiency 58,2%, actual steam rate 8,23 kg/kwh (calculation). Many effort should be taken to increase the power plant performance by improving the operational parameter of the equipment as well as biomassfuel properties and treatment.